Claw shape variation in oribatid mites of the genera Carabodes and Caleremaeus : exploring the interplay of habitat, ecology and phylogenetics - Kerschbaumer, Michaela; Schäffer, Sylvia; Pfingstl, Tobias (PeerJ (San Francisco, CA), 2023)
Background Claws are a commonly observed biological adaptation across a wide range of animal groups. They serve different functions and their link to evolution is challenging to analyze. While there are many studies on the comparative anatomy and morphology of claws in reptiles, birds and several arthropods, knowledge about claws of soil-living oribatid mites, is still limited. Recent research on intertidal oribatid mites has shown that claw shape is strongly correlated with microhabitat and is subject to ecological selective pressures. However, the selective constraints shaping claws in terrestrial oribatid mites are still unknown. Methods In this study, 300 specimens from 12 different species and two genera were examined. Geometric morphometrics were used to quantify claw length and curvature, and to analyze two-dimensional claw shape. In combination with molecular phylogenetic analyses of investigated populations phylogenetic signal was quantified within genera using Blomberg's K and random replicates. Additionally, ecological information on the investigated species was gathered from previous studies and compiled into tables. Results The claw shapes of Carabodes species vary moderately, with the three species C. reticulatus, C. rugosior and C. tenuis deviating the most from the others. These three species are only found in a small number of habitats, which may require a more specialized claw shape. Our results show that there is a phylogenetic influence on claw shape in Carabodes but not in Caleremaeus. Additionally, habitat specificity and lifestyle were found to have ecological impact on claw shape in both genera. The present results demonstrate that characteristics of the claws of terrestrial oribatid mites are correlated with ecology, but this correlation is apparently weaker than in intertidal oribatid mites that are prone to strong external forces.